Aspects that influence access to financial services among Arequipa region households - Mamani Lopez, Jiang Wagner (2022)
The development of a solid financial system that drives economic growth is of utmost importance to generate improvements in the levels of social welfare of a country or region. According to figures estimated by the National Institute of Statistics and Informatics (INEI), in the Arequipa region there is still a high percentage of people who do not use formal financial services. In this way, policies that promote financial inclusion emerge as a fundamental piece to provide equal opportunities for access to financial services in those households with low-income levels. For this reason, this article was for determine whether economic and sociodemographic aspects significantly influence access to financial services in households in the Arequipa region, using econometric models with binary dependent variables (logit and probit). The information comes from the National Household Survey (ENAHO), taking into account a total sample of 1781 households for that region. The results allowed us to conclude that access to financial services in households in the Arequipa region is mainly influenced by: having an employment contract, being affiliated with the pension system, having private health insurance, having internet access, own cell phone and an increase in income level.